2003
DOI: 10.1029/2002jc001360
|View full text |Cite
|
Sign up to set email alerts
|

Formation and circulation of dense water in the Persian/Arabian Gulf

Abstract: [1] The nature and circulation of water masses in the Persian/Arabian Gulf (hereinafter referred to as the Gulf ) is investigated by examination of a historic database of hydrographic observations. The densest water forms in winter at the northern end of the Gulf rather than along the warmer southern and western coasts. With the exception of small amounts of water directly above the seafloor, most water flowing out of the Gulf mixes across a density front that separates Gulf Deep Water within the Gulf from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
141
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(159 citation statements)
references
References 25 publications
16
141
2
Order By: Relevance
“…This water mass, called PGW (Persian Gulf Water), with salinity above 40 psu, flows into the Sea of Oman via the Strait of Hormuz. The density of the outflowing PGW varies seasonally, the densest water being formed in winter (Swift and Bower, 2003). In the Sea of Oman, the PGW outflow equilibrates around 250 m depth, mixing with the fresher Indian Ocean Central Water (IOCW).…”
Section: Introductionmentioning
confidence: 99%
“…This water mass, called PGW (Persian Gulf Water), with salinity above 40 psu, flows into the Sea of Oman via the Strait of Hormuz. The density of the outflowing PGW varies seasonally, the densest water being formed in winter (Swift and Bower, 2003). In the Sea of Oman, the PGW outflow equilibrates around 250 m depth, mixing with the fresher Indian Ocean Central Water (IOCW).…”
Section: Introductionmentioning
confidence: 99%
“…Large evaporation rates over the Gulf lead to the formation of a warm and salty water mass (Persian Gulf Water, PGW) which flows into the Gulf of Oman through the Strait; the mass and salt budget in the Gulf are closed by an inflow of Indian Ocean Surface Water (IOSW) coming from the northern Gulf of Oman, and also by evaporation and by river discharge. Indirect estimates of this exchange flow through the Strait [Sultan and Ahmad, 1993;Bower et al, 2000;Swift and Bower, 2003] suggested its high variability. More recently, data collected in the Strait of Hormuz show that if the thermohaline properties of the water masses undergo significant changes on the seasonal timescale, currents (at least of the out-flowing PGW) have, on the contrary, remarkably low variability [Johns et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, data collected in the Strait of Hormuz show that if the thermohaline properties of the water masses undergo significant changes on the seasonal timescale, currents (at least of the out-flowing PGW) have, on the contrary, remarkably low variability [Johns et al, 2003]. At the head of the Gulf of Oman, the salinity of outflowing PGW is reduced by mixing with IOSW [Banse, 1997;Matsuyama et al, 1998;Swift and Bower, 2003]. High rates of mixing are mainly attributed to topographic effects and to internal waves (with amplitudes reaching 20 m).…”
Section: Introductionmentioning
confidence: 99%
“…This inflow penetrates into the Gulf and is carried northwards along the Iranian coast, gradually increasing in salinity to more than 40 psu (Michael Reynolds 1993). The inflow is seasonal, with maximum in late spring (Swift & Bower 2003), when it spreads as far as the north-western part of the Gulf.…”
Section: Study Areamentioning
confidence: 99%
“…The Shatt Al-Arab discharge is expected to amplify the Saudi-Emirate coastal current (Michael Reynolds 1993); its influence is especially evident along the south-western Gulf coast from Iraq to Qatar. Deep part of the Gulf is characterized by pronounced haline stratification (Michael Reynolds 1993;Swift & Bower 2003). In contrast, water column in the shallow (<10-15 m) northern, western and southern Gulf is well mixed as a result of wind stress and tidal turbulence (John 1992).…”
Section: Study Areamentioning
confidence: 99%